(untitled) (Al-Academy, 2021)
This research means a study (the impact of the Arab-Islamic environment on contemporary painting, the artist Abd al-Rahman al-Suleiman as a model). The research falls into two axes: the first: the theoretical axis, and the second: the applied axis. The first axis dealt with an introduction that contained: (the research problem, its importance, its goal, its limits, and the definition of terms). This research aims to uncover (the impact of the Arab-Islamic environment on contemporary painting, and the artist Suleiman was a model). And the research limits spatially: Saudi Arabia, and temporally: 2010-2014. This theme included two topics: The first: the characteristics of the Saudi environment and its impact on art. The second: the style of the Suleiman artist. As for the second (application) axis, it was represented by the research procedures, and then the study was concluded with the results and sources on which this study relied.